Structural Analysis of Muscarinic Acetylcholine Receptor Type 1 Intracellular Loop 3 by Hydrogen/Deuterium Exchange Mass Spectrometry - Y. Ko, In; K. Kim, Dong; Y. Chung, Ka (Protein and Peptide Letters, 2015)
G protein-coupled receptors (GPCRs) perform vital signaling functions and are involved in various diseases, making GPCRs major drug targets. GPCRs have seven α-helical transmembrane domains connected by three extracellular loops (ECLs) and three intracellular loops (ICLs). Among the three ICLs, ICL3 has been reported to have a critical function in interacting with downstream signaling molecules. Despite its important role in GPCR signaling, the structure of ICL3 has not been fully defined. In the present study, we used muscarinic acetylcholine receptor type 1 (M1) as a model system to analyze the structure of ICL3. Optimized purification conditions for M1_ICL3 comprised His-tag affinity purification and solubilization with n-dodecyl-b-D-maltopyranoside. Purified M1_ICL3 was analyzed using circular dichroism and hydrogen/deuterium exchange mass spectrometry; the results of these analyses suggested that M1_ICL3 is disordered and flexible.
Keywords: intracellular loop 3